Investigation of the Gas Atoms Interaction with BC Nanotube - S. Boroznin; I. Shanaev; I. Zaporotskova; N. Polikarpova (Журнал нано- та електронної фізики)
In this article we represent the theoretical research of the sorption properties for two types of boron-carbon nanotubes (BCNTs) using the scheme of an ionic-built covalent-cyclic cluster model and MNDO quantum chemical method. We investigated the process of Cl, O, F sorption on the surface of single-walled BC nanotubes arm-chair type. The optimal geometry of the sorption complexes and the sorption energy values have been obtained.